Exploring the Efficacy of Reward Systems for Generation Z and Millennials: A Systematic Literature Review - Alimin, Ismet; Tukiran, Martinus (International Journal of Social and Management Studies, 2024)
In the world of work that continues to develop, generation Z (1997-2012) and millennials (1981-1996) dominate the global workforce. Understanding their preferences for reward systems is key to increasing job satisfaction, employee retention and organizational performance. An effective reward system can influence motivation and productivity, however, the needs and expectations between these two generations can differ significantly. This study aims to explore and analyze the effectiveness of various reward systems applied to generation Z and millennials. The focus is on identifying reward preferences, measuring the impact of innovative versus traditional reward systems, and evaluating how personalizing rewards can increase motivation and performance. Using the PICOS (Population, Intervention, Comparison, Outcomes, Study design) framework, we conducted a systematic literature review (SLR) on research published in highly reputable journals. Data is collected from a variety of academic sources spanning both quantitative and qualitative studies, including surveys, experiments, and meta-analyses. Findings show that Generation Z and millennials have different reward preferences in the modern work environment. Generation Z values instant recognition and feedback, which is a result of their upbringing in a hyper-connected, technology-based environment. They prefer rewards that are quick and easy to access, such as digital recognition and praise on company social media. Millennials, while also appreciating feedback, place greater importance on formal recognition and long-term career development opportunities, such as upskilling and promotions. Generation Z values flexibility in work, including work-from-home options and flexible work schedules, to fit work into their personal lives. Millennials are focusing more on work-life balance policies that support their overall well-being, such as flexible leave and mental health policies. Both generations prioritize a balanced life experience where work does not dominate their personal lives. Technology-based reward systems may be more effective in increasing job satisfaction and employee retention for Generation Z compared to millennials. However, further research is needed to confirm this.